Probing Silicon Lithiation in Silicon-Carbon Blended Anodes with a Multi-Scale Porous Electrode Model. Issue 12 (7th August 2020) - Lory, P-F; Mathieu, B.; Genies, S.; Reynier, Y.; Boulineau, A.; Hong, W.; Chandesris, M.
Abstract : Blended negative electrodes with a mix of graphite and silicon are attractive solutions to extend the energy density of lithium-ion batteries. Given the huge volume expansion of silicon, the relative lithiation/delithiation of both active materials upon cycling is crucial to determine the mechanical behavior of the electrode. It is complicated however by the potential hysteresis displayed by silicon. We focus on a blended anode with 16 wt% of silicon carbon composite (SiC-C) at a gravimetric capacity of 1500 mAh.g −1 mixed with 84 wt% graphite. A multi-scale porous electrode model with three different hierarchical units has been developed to account for the morphology of the SiC-C composed of nanoflakes of silicon embedded in a carbon matrix. The developed physics-based model is parametrized with appropriate experiments and validated for two electrodes loadings and various operating conditions. The validated model allows to probe the lithiation competition between the silicon and the carbon within the composite and the graphite. It is able to capture the streaking features revealed by synchrotron experiments. In particular, we show that at higher C-rates, the lithiation of the silicon is delayed and reduced compared to the graphite one. Quantifying this relative competition is valuable as aging effects are significantly accelerated by the expansion of the silicon.